2013
DOI: 10.1051/0004-6361/201321128
|View full text |Cite
|
Sign up to set email alerts
|

Long term variability of Cygnus X-1

Abstract: We present a scheme for determining the spectral state of the canonical black hole Cyg X-1 using data from previous and current X-ray all sky monitors (RXTE-ASM, Swift-BAT, MAXI, and Fermi-GBM). Determinations of the hard/intermediate and soft state agree to better than 10% between different monitors, facilitating the determination of the state and its context for any observation of the source, potentially over the lifetimes of different individual monitors. A separation of the hard and the intermediate states… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
150
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(166 citation statements)
references
References 46 publications
(69 reference statements)
16
150
0
Order By: Relevance
“…The total exposure time of our observations is 4.77 Ms which corresponds to ∼10 orbital periods of 5.6 d. The exposure is evenly distributed between the orbital phases. Advances in PCA calibration (Shaposhnikov et al 2012) and a careful consideration of energy-dependent systematic uncertainties in different gain epochs of the PCA instrument Grinberg et al 2013) strengthen our analysis. For a detailed discussion of data treatment, see Grinberg et al (2013).…”
Section: Data and Spectral Analysismentioning
confidence: 62%
See 4 more Smart Citations
“…The total exposure time of our observations is 4.77 Ms which corresponds to ∼10 orbital periods of 5.6 d. The exposure is evenly distributed between the orbital phases. Advances in PCA calibration (Shaposhnikov et al 2012) and a careful consideration of energy-dependent systematic uncertainties in different gain epochs of the PCA instrument Grinberg et al 2013) strengthen our analysis. For a detailed discussion of data treatment, see Grinberg et al (2013).…”
Section: Data and Spectral Analysismentioning
confidence: 62%
“…Boroson & Vrtilek (2010) classified 102 of these observations as hard states and used them to demonstrate the orbital variability of absorption in the hard state, but did not have enough data taken during softer states. At the same time, higher sensitivity snapshots at different φ orb with Chandra (Miller et al 2005;Hanke et al 2009;Miškovičová et al 2015) and Suzaku Miller et al 2012;Yamada et al 2013) revealed a complex structure of the wind with highly Grinberg et al (2013).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations